PENINGKATAN DAYA SAING MASYARAKAT: PEMBUATAN KAIN KANVAS LUKIS DENGAN TEKNIK PELABURAN MENGGUNAKAN LITHOPON DI PESANTREN RANCA HERANG, DESA CIBOGO, BANDUNG - Wawan Suryana; Ariesa Pandanwangi; Ismet Zainal Effendi; Sharon Elnissi; Farhan Deniansha (JUARA: Jurnal Wahana Abdimas Sejahtera, 2021)
Cibogo Village, Kodya Bandung is located behind the Maranatha Christian University campus. The village has a Islamic boarding school (Pondok Pesantren) Ranca Herang which is currently actively inhabited by students and female students. These students focus on studying religion, at the end of the year they are always ready to go into society and be independent. On that basis, the pesantren submitted a letter to the Fine Arts Study Program with the aim of getting training from lecturers and students, namely skills that can increase community competitiveness. The method of implementing this activity uses mentoring methods and practical methods. This activity is in the form of training in making painted canvas cloth with the laying technique using a lithophone. This solution was given because the large number of requests for canvas from schools in the city of Bandung had not been fulfilled. Apart from providing training, this program also provides insight into the tools and materials for creating fine arts. The results of this training are carried out in stages and the results show that they are able to make canvas cloth practically, it is hoped that those who acquire these skills will later become provisions to earn a living from making canvas paintings so that they can improve their standard of living, over life, during life community life.